Effect of bulk and nanoparticle Bi2O3 on attenuation capability of radiation shielding glass. Issue 14 (15th July 2021) - Elsafi, M.; El-Nahal, M.A.; Sayyed, M.I.; Saleh, I.H.; Abbas, M.I.
Abstract: The aim of this study is to examine the effect of Bi2 O3 concentration and particle size on Bi2 O3 glass. The tested glasses had the composition of SiO2 –Bi2 O3 –CaO–MgO–B2 O3 –K2 O–Na2 O–ZnO. Ordinary glass was compared with glasses with 10% Bulk Bi2 O3, 10% Bi2 O3 Nanoparticles (NPs), 20% Bulk Bi2 O3, and 20% Bi2 O3 nanoparticles. The mass attenuation coefficients (MACs) of all the investigated glasses were determined between 0.0595 MeV and 1.41 MeV. The results demonstrated that increasing the Bi2 O3 content in the glass matrix improved their shielding capability, as well as showing that the NPs provided greater attenuation than the bulk Bi2 O3 at the same concentration. The percent increase in the MAC between the bulk and nano Bi2 O3 was also calculated and analyzed. From the MAC values, the LAC of the glass was determined and similar results were found compared to the MAC figure. The HVL and MFP of the glass were then analyzed and the results demonstrated that the glass with Bi2 O3 NPs attenuated the same amount of photons at a smaller thickness, making the NP shield more effective. The heaviness of the samples illustrated that all the tested samples have a smaller weight than pure lead, making them more desirable. The attenuation factor of the glass (Att. Factor %) showed that increasing the Bi2 O3 content in the samples and increasing the thickness of the shields both improve the shielding capability of the glass. Lastly, the dlead of the glasses was determined, indicating that the greatest reduction in thickness occurs near the K-absorption edge of bismuth. Overall, the glass with 20% Bi2 O3 NPs demonstrated to have the greatest potential for radiation shielding applications.